Analysis of Service Quality Satisfaction of E-KTP Service at Public Administration and Civil Registration Office of Bogor District - Rizq, Shafira; Djamaludin, Moh Djemdjem; Nurhadryani, Yani (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
The purpose of this study was to analyze the satisfaction of service quality in the E-KTP service of the Bogor District Population and Civil Registration Service. The design of this study was a cross-sectional study at Disdukcapil Bogor District. The method used in this study is Servqual, importance performance analysis (IPA), and customer satisfaction index (CSI) with 100 respondents selected using a convenience technique. The result of customer satisfaction index analysis shows that the community has been